Implementation of Khiyar Rights in Online Buying and Selling on Shopee Tokba.id Sellers - Farihmatul Hasanah, Mimah; Sucipto , Moch. Cahyo; Sopian, Ahmad Ali (EKSISBANK (Ekonomi Syariah dan Bisnis Perbankan), 2023)
Buying and selling is not only done offline, but also online. Shopee marketplace online transactions have more potential for the process of implementing khiyar rights, namely there are several factors that can allow continuing or canceling transactions. One of the users of the shopee marketplace is the Tokba.id shop. Buying and selling at the Tokba.id store can also be done with a wholesale system, this wholesale system is considered prone to errors because the goods ordered are more numerous and the process of checking the goods will be more difficult, so the risk of defective or damaged goods is greater. The purpose of this study is to analyze the application of khiyar rights in the process of buying and selling Tokba.id products on the shopee marketplace. This research uses a descriptive qualitative approach. With data collection techniques, namely observation, interviews, and documentation. Informants were determined using Purposive Sampling, namely the owner and manager of Tokba.id. The results of this study conclude that the buying and selling process at the Tokba.id store includes several stages, namely the product sales process and the product purchase process. Meanwhile, the implementation of khiyar rights at the Tokba.id store is in accordance with several khiyars which are the focus of this research, namely khiyar conditions at the Tokba.id store imposing returns with several conditions that have been imposed by shopee and also the Tokba.id store such as the buyer receiving the goods ordered, the buyer can submit a return of goods with approximately 3 days of the shopee warranty period. Khiyar 'aib by enforcing returns if there are 'aib or defects in the goods received such as errors in size, color. Khiyar ru'yah at the Tokba.id shop, namely the seller applies for the return of goods, if the buyer buys goods that are received not according to the description listed on the Tokba.id shopee storefront. Khiyar ta'yin at the Tokba.id store, buyers can check the availability of goods at the Tokba.id storefront which includes color, size. Meanwhile, khiyar majlis at the Tokba.id store cannot be applied. Because there is no place or majlis which is used as a meeting place for the two parties to the contract or sale and purchase transaction.